2020
DOI: 10.21203/rs.3.rs-28067/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interaction of MC4R rs17782313 variants and dietary carbohydrate quantity and quality on basal metabolic rate and general and central obesity in overweight/obese women: a cross-sectional study

Abstract: Background Recent studies have shown that dietary carbohydrate quantity and quality as well as genetic variants may contribute to determining metabolic rate and general and central obesity. This study aimed to examine interactions between melanocortin 4 receptor gene (MC4R) rs17782313 and dietary carbohydrate intake, glycemic index (GI), and glycemic load (GL) on body mass index (BMI), waist circumferences (WC), basal metabolic rate (BMR), and BMR/kg in overweight/obese women. Methods A total of 282 Iranian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…All products were visualized by agarose gel electrophoresis. Then, fragments containing three genotypes were distinguished: CC, CT, and TT [51].…”
Section: Dna Extraction and Sequencing Of The Genementioning
confidence: 99%
“…All products were visualized by agarose gel electrophoresis. Then, fragments containing three genotypes were distinguished: CC, CT, and TT [51].…”
Section: Dna Extraction and Sequencing Of The Genementioning
confidence: 99%
“…Furthermore, most studies in this area of research have been conducted in Western countries where red meat consumption has been reported to be high, while people living in the Middle East, have a special pattern of consumption. Iranian people consume a large amount of carbohydrates in their usual diets [19] and have a higher intake of full-fat red meats, compared to other meats [8]. Moreover, the intake of fish per capita in Iran is lower than the international standard [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the MC4R gene is the most prevalent monogenic cause of obesity [6,7], with a prevalence of 1.7-3.0% among obese people [8]. In this sense, the variant rs17782313 near the MC4R gene has been strongly linked with obesity [9,10] and showed a significant association with dietary intake [11][12][13], total energy intake [14], increased snacking, as well as hunger [15].…”
Section: Introductionmentioning
confidence: 99%